An ultra-sensitive wearable multifunctional flexible sensor with a self-assembled dual 3D conductive network and yeast-foamed silicone rubber foam. Issue 42 (11th October 2022) - Lu, Yao; Zhao, Dongqing; He, Junwei; Zou, Liming; Wang, Jincheng; Song, Shiqiang
Abstract : In this work, we developed a series of sensors based on silicone rubber foam and dual 3D conductive networks, which exhibit ultra-high sensitivity, low detection limits and a wide detection range for tensile strain, pressure and temperature. Abstract : Flexible wearable sensors are actively used in the fields of sensing skin, human motion detection and healthcare monitoring. However, most wearable sensors generally suffer from poor mechanical properties, low sensitivity and single detection function. Here, a multifunctional flexible Dual-SF sensor with ultra-high sensitivity and a wide detection range for stretch and pressure is reported based on silicone rubber foam and a dual interconnected conductive network. The resultant Dual-SF sensor has a high sensitivity (gauge factor (GF) up to 690.76 and pressure sensitivity ( S ) up to 169.94 kPa −1 ), low detection limit (0.2% strain and 1.274 Pa pressure) and excellent durability, and is able to detect both weak and large movements of the human body. On this basis, large-area meshed sensors and sensor arrays were fabricated by hollow design and multiple flexible sensor integration, respectively, for detecting muscle group contractions and the spatial distribution of pressure. Additionally, the Dual-SF/LSR sensor prepared by backfilling pores with liquid silicone rubber (LSR) has a high temperature coefficient of resistance (TCR, 0.01621 °C −1 ) and realizes application in skin and machine temperature measurements. These superior properties lay a foundation for the application of Dual-SF in the fields of human motion detection, health monitoring and electronic skin.